Creating Scenes for an Intelligent Nursing Environment: Co-design and User Evaluations of a Home Control System - Kymalainen, T.; Heinila, J.; Tuomisto, T.; Plomp, J.; Urhemaa, T. (2012 8th International Conference on Intelligent Environments, 2012)
In this paper we describe the co-design process of a proof-of-concept home control system, and how it was carried out by utilising a user-centred design methodology. The aim was to develop a demonstrator of a home control system that supports elderly people in living more independently in their homes. The focus of the research was on the configuration tool of the environment, which was meant to be exploited in a nursing home. The home control system was intended to be used and configured by non-technologically versed users: mainly the care personnel, but also the inhabitants and their close relatives. The system was co-designed and evaluated at first with nurses, who were considered to be the local experts of the chosen ecosystem. The final web-based proof-of-concept system was evaluated with nurses and end-users.